Effect of Installation Pattern of Prefabricated Vertical Drain (PVD) on Degree of Consolidation in Soft Soils - Liliwarti, Liliwarti; Archenita, Dwina; Misriani, Merley; Refnaldo, Afdal (Jurnal Fondasi, 2023)
Soft soil has high water content and low permeability, causing a high settlement and long time. Soil improvement with prefabricated Vertical Drain (PVD) can accelerate settlement in soft soils and primary consolidation time. Prefabricated Vertical Drain (PVD) functions to accelerate the release of water from the ground, and the accelerated settlement process, which is indicated by the degree of consolidation (U) reaching 90%, generally this method combines PVD and preloading (additional load). The required time to achieve a 90% degree of consolidation is determined by the PVD installation pattern (triangle pattern and rectangular pattern) and its distance. This study reviewed the effectiveness of PVD installation patterns with distance variations of (1 m, 1.3 m, 1.6 m, 1.9, 2.2 m, 2.5 m, 2.8 m, and 3.1 m). The analysis results show that in the triangular pattern, the time required to achieve a degree of consolidation of 90% (U90) is from 1 to 8.5 months, and in the rectangular pattern is from 1 to 9.5 months. The greater distance between PVDs, the more time is required to achieve a 90% degree of consolidation (U90). The PVD with a triangular pattern could reduce the 6% - 25% time to complete a degree of consolidation (U90) compared to the rectangular pattern. It can be noted that the installation triangle pattern is more effective than the rectangular installation pattern.